(untitled) (SCIENCE TIME JOURNAL, 2026)
In contemporary cognitive linguistics, the concept is regarded as a key mental construct mediating between language, cognition, and culture. This article explores the theoretical distinction between linguistic concepts and temporal concepts, emphasizing their different ontological status and modes of linguistic realization. The nucleus–periphery model is applied to reveal the internal structure of the temporal concept and its universal and culture-specific components. Based on English and Karakalpak fairy-tale discourse, the analysis shows that temporal meanings are frequently realized symbolically through narrative formulas rather than through chronological reference. The findings highlight the necessity of distinguishing between cognitive models of time and their linguistic manifestations in order to ensure methodological precision in conceptual and discourse-oriented research.